Civil Liability for Environmental Damage in Indonesia: An Assessment of Carbon Trading Mechanism's Role for Corporate Responsibility Promotion - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Hidayat, Ahmad (Westscience Press, 2025)
The paper discusses civil liability for environmental damages in Indonesia, considering the carbon trading mechanisms role in promoting corporate responsibility. Hence, this research has adopted a normative approach, analyzing the existing juridical framework that governs environmental damage and discussing to what extent carbon markets, among other emissions trading systems or carbon taxes, can serve complementary functions of incentivizing corporations toward environmentally responsible behavior. The study identifies loopholes within Indonesia's legal system, particularly for the enforcement of environmental liability laws, and discusses how carbon trading could supplement these deficiencies through financial incentives for reducing emissions. The results show that while the mechanisms of carbon trading hold great potential to promote corporate responsibility, their effectiveness relies on robust market infrastructure, sound systems of monitoring and verification, and integration with existing policies on the environment. The study also finds that to enhance corporate environmental accountability in Indonesia, a combination between legal liability and market-driven incentives is essential.